Transforming Arabic Language Learning: A PBL Approach to Cultivating Student Engagement - Ulfah Nur Fadhila; Najih Anwar (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The learning process in many schools remains dominated by the lecture method, causing students to become passive and less motivated to learn. An effective alternative is the Project-Based Learning (PjBL) model, which promotes active engagement through meaningful project activities. This study aimed to examine the implementation of the PjBL model in Arabic language learning and to evaluate its effectiveness in increasing the learning interest of Grade VIII students at MTs Al Ihsan Sungai Rumbai, Bengkulu. The research used a participatory Classroom Action Research (CAR) approach following the Kurt Lewin model, consisting of four stages: planning, implementation, observation, and reflection. The study involved 28 Grade VIII students as participants. Data were collected through observation, questionnaires, interviews, and documentation, then analyzed using percentage calculations based on the Likert scale to measure changes in learning interest. The results indicated a significant improvement in students’ interest, increasing from 62% in the pre-cycle (low) to 78% in Cycle I (moderate) and 89% in Cycle II (good). These findings demonstrate that the PjBL model fosters a more active, collaborative, and meaningful learning environment. Therefore, Project-Based Learning is considered an effective and applicable strategy to enhance students’ interest in learning Arabic at the madrasah tsanawiyah level.